2014
DOI: 10.1073/pnas.1402926111
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the recruitment of glycogen synthase by glycogenin

Abstract: Glycogen is a primary form of energy storage in eukaryotes that is essential for glucose homeostasis. The glycogen polymer is synthesized from glucose through the cooperative action of glycogen synthase (GS), glycogenin (GN), and glycogen branching enzyme and forms particles that range in size from 10 to 290 nm. GS is regulated by allosteric activation upon glucose-6-phosphate binding and inactivation by phosphorylation on its N-and C-terminal regulatory tails. GS alone is incapable of starting synthesis of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(86 citation statements)
references
References 35 publications
9
77
0
Order By: Relevance
“…The structure of Ce GS showed that the N-terminal phospho-sites are positioned in such a way that they can interact with the regulatory helix 13 . The phospho-sites, Ser12 and Thr19 are separated from the cis-regulatory helix by only 6–16 Å 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of Ce GS showed that the N-terminal phospho-sites are positioned in such a way that they can interact with the regulatory helix 13 . The phospho-sites, Ser12 and Thr19 are separated from the cis-regulatory helix by only 6–16 Å 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The structure of Ce GS showed that the N-terminal phospho-sites are positioned in such a way that they can interact with the regulatory helix 13 . The phospho-sites, Ser12 and Thr19 are separated from the cis-regulatory helix by only 6–16 Å 13 . The authors proposed that upon phosphorylation, the N-terminal tail could dissociate itself from its ordered position and engage with the charged arginine residues 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miglustat for the treatment of Gaucher disease (Platt and Jeyakumar 2008)) to reduce the consequence of toxic metabolite accumulation due to defective enzymes (Schiffmann 2015). We anticipate that progress in the structural biology of GYS and GYG (Chaikuad et al 2011; Zeqiraj et al 2014) should pave the next step forward in developing novel inhibitors for these enzymes. This example therefore illustrates the principle of targeting different components of a metabolic pathway for the treatment of a genetic disease.…”
Section: Multiple Intervention Avenues Within a Metabolic Pathwaymentioning
confidence: 99%
“…Although the crystal structure has not been published for any mammalian GS, the structures for a bacterial GT5 synthase ( Agrobacterium tumefaciens ) [2] and, more recently, for a yeast synthase ( Saccharomyces cerevisiae ; Gsy2p) [26] and a Caenorhabditis elegans synthase [27] have been solved. Yeast GS is a homo-tetrameric protein in both its basal and active states and eukaryotic GT3 synthases likely have a similar tetrameric arrangement due to their high sequence identity [26].…”
Section: Introductionmentioning
confidence: 99%